An Analytical Study of Farmers' Response to the Effect of Prices Fluctuations and Rain Precipitation Changes on the Area of Chickpeas in Al-swaida'a Governorate (Damascus University Journal of agriculture sciences, 2026)
The study aimed to analyze the farmers` response to the effect of prices fluctuations and rain precipitation changes on the area of chickpeas in Al-swaida`a Governorate during the period 2000-2021, to find out the most important factors affecting their decisions.Depending on relationship analysis between the risk factor (as a dependent variable) and some of the personal qualities, economic and social characteristics (as independent variables), through the use of sports program SPSS.The results showed that the most important factors affecting on the risk factor for chickpeas were the average product of the chickpeas, and then the area planted with the lentils for the same year of study 2020/2021. As for determining the impact of some economic and climatic variables in the area of chickpeas, been counting on the Nirlove model. The model included the cultivated areas as a dependent variable while the cultivated area, the price of the crop and its productivity, the price of the previous competing crop, and the price and production risk for the previous year as independent variables.The results showed that the economic and climatic variables in the area had significant impact on the area of chickpeas in Al-swaida`a Governorate percent 46%.The results showed that the Utility Function was a concave shape for those willing to take risks, and a straight shape for those neutral to risk, while it was a convex shape for chickpeas growers unwilling to take risks, within the study sample at 2021.
Keywords: Chickpeas; Prices Fluctuations; Rain Precipitation; Nirlove Model